Beliefs Of Chronic Kidney Disease Patient: A Phenomenology Study - Euis Dedeh Komariah; Kristia Novia; Rosmina Situngkir; Nikodemus Sili Beda (Babali Publisher, 2023)
Introduction: Kidney failure is a chronic disease with various triggers and has an impact on the decline in kidney function quickly and ends with chronic kidney failure. Chronic kidney failure is a world issue that cannot be separated from influence of culture, beliefs, and spirituality from the community. This to explore the culture, beliefs, and spirituality of patients with chronic kidney disease in Makassar, South Sulawesi, Indonesia. Methods: This study used a qualitative study with ten participants with chronic kidney disease who underwent dialysis. The sampling technique used is purposive sampling, with data analysis used Collaize method. Results: Results of this study in two themes, namely: alternative medicine and accepting the situation. Conclusion: Patients with chronic kidney diseases take treatment using traditional herbs, seek treatment at traditional healers, and increase their spirituality with God after being diagnosed chronic kidney disease. It is necessary to improve the ability of nurses in providing nursing care, especially mental health services, spirituality and assistance to patients in the process of accepting conditions and the ability to adapt optimally.